A framework for assessing impacts of wild meat hunting practices in the Tropics - Dobson, A; Milner-Gulland, E; Keane, A; Ingram, D (Springer Verlag, 2019)
Terrestrial wildlife is being hunted for consumption by humans in the tropics at an unprecedented rate, and the often unsustainable nature of this harvest has profound implications not only for biodiversity and ecosystem function, but also for human livelihoods. Whilst the nature and impacts of this practice have been studied in numerous contexts and localities, a comprehensive treatment of the social, economic, and environmental determinants of both hunter decision-making and hunting outcomes has been lacking. In this review we discuss influences of hunting methods and effort on the types of animals caught, the efficiency of harvest, and the implications of these factors for sustainability. We highlight gaps in current understanding, and identify the most important data requirements. Our approach provides a framework for the design of future studies into wild meat hunting and its impacts, promoting the efficient targeting of priority areas of research.